(untitled) (Journal Of Educational and Psychological Researches, 2019)
In the spreading of the Internet, mobile smart devices, and interactive websites such as YouTube, the educational video becomes more widespread and deliberative among users. The reasons for its spread are the prevalence of technologies, cheap cost, and easy to use. However, these products often lack to the distinction in video production. By following videos of an educational channel on YouTube, some comments found to discuss the lack of the content presented to motivate the learners, which lead to reduce the viewers of the videos. Therefore, there is an important decision to find general standards for the design and production of educational videos. A list of standards has been drawn up to help those interested in producing educational videos to stimulate learner motivation, after reviewing 65 documents related to the field of educational video design and multimedia. The list contained three main fields: educational, authentication, and technical. The educational field contained the following standards: (Work Title, Goals, Content Presentation, Content Elements, and Motivational Activities). While the authentication field contained the following standards: (Intellectual Rights and Personality Traits). Finally, the technical field contained the following standards: (Shooting Footage, Lighting, Sound, Texts, final product, and Time/Duration).